2018
DOI: 10.1007/s10557-018-6825-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Major Bleeding Among Working-Age Adults with Atrial Fibrillation: Evaluating the Effects of Potential Drug-drug Interactions and Switching from Warfarin to Non-vitamin K Oral Anticoagulants

Abstract: Purpose This study aims to evaluate the associations between switching from warfarin to non-vitamin K oral anticoagulants (NOACs), exposure to potential drug-drug interactions (DDIs), and major bleeding events in working-age adults with atrial fibrillation (AF). Methods We conducted a retrospective cohort study using the claims database of commercially insured working-age adults with AF from 2010 to 2015. Switchers were defined as patients who switched from warfarin to NOAC; non-switchers were defined as tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Oral anticoagulants, which must be taken for life after mechanical valve replacement, show therapeutic effects by maintaining adequate blood levels with the international normalized ratio (INR) of prothrombin time (PT) depending on the valve location. According to racial and sociocultural characteristics, low-dose anticoagulant therapy is recommended for Asians based on coagulation characteristics, lifestyle (including food), interactions with other drugs, and vulnerable thrombotic complications [ 2 , 3 ]. Oral anticoagulant therapy after mechanical valve replacement in Koreans requires more detailed, systematic, and continuous management [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral anticoagulants, which must be taken for life after mechanical valve replacement, show therapeutic effects by maintaining adequate blood levels with the international normalized ratio (INR) of prothrombin time (PT) depending on the valve location. According to racial and sociocultural characteristics, low-dose anticoagulant therapy is recommended for Asians based on coagulation characteristics, lifestyle (including food), interactions with other drugs, and vulnerable thrombotic complications [ 2 , 3 ]. Oral anticoagulant therapy after mechanical valve replacement in Koreans requires more detailed, systematic, and continuous management [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study done by Feng et al in adult AF patients, it was found that potential drug-drug interactions were significantly lower in those who switched from warfarin to DOACs. 20 We found that patients above 60 years and presence of VTE were significant predictors of major drug interactions. However, the results of the multivariate analysis should be viewed with caution owing to the small sample size and single study centre.…”
Section: Discussionmentioning
confidence: 73%
“…3 Feng et al reported that the number of potential drug interactions and the proportion of days with potential drug interactions were significantly associated with risk of bleeding. 20 In the excessive warfarin anticoagulation (EWA) study done in AF patients, excessive alcohol consumption and reduced renal function were the strongest predictors of excessive warfarin anticoagulation, defined as INR values≥9. Recent intake of antibiotic or antifungal drugs, recent hospitalization and outpatient visit were the other significant temporary predictors of excessive anticoagulation with warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…Warfarin, a vitamin K antagonist, interacts with numerous drugs and foods, and the list of interactions continues to expand. [ 24 ] Controlling anticoagulants is important for patients after mechanical valve replacement because maintenance of the correct target PT INR is essential to maintain valve function. Prescription of non-vitamin K antagonist oral anticoagulants has increased dramatically since their introduction in 2010.…”
Section: Discussionmentioning
confidence: 99%